2019
DOI: 10.1111/een.12756
|View full text |Cite
|
Sign up to set email alerts
|

Response of passerine birds and chicks to larvae and pupae of ladybirds

Abstract: 1. Few, if any, experimental tests have demonstrated the anti‐predator protection of the developmental stages of ladybirds (Coleoptera: Coccinellidae) against vertebrates, despite the fact that both the visual appearance of ladybirds and the content of defensive compounds fulfil the definition of an aposematic prey. 2. In this study, avian predators of three species were confronted with fourth‐instar larvae and pupae of the harlequin ladybird (Harmonia axyridis) – a large, conspicuous, and toxic ladybird speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The results of the current study confirm the avoidance of H. axyridis larvae by experienced wild birds during the breeding season, and in an aviary by naïve birds, and quantify the predation rate of aposematic larvae in comparison to less aposematic and cryptic larvae. In the same study (Aslam et al, ), tree sparrows attacked and ate moderate numbers of ladybird larvae. It was previously shown that P. montanus ate ladybirds without significant physiological problems, whereas cadavers of P. major from the same experiments showed evidence of severe liver damage (Kristin, ; Marples et al, ).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The results of the current study confirm the avoidance of H. axyridis larvae by experienced wild birds during the breeding season, and in an aviary by naïve birds, and quantify the predation rate of aposematic larvae in comparison to less aposematic and cryptic larvae. In the same study (Aslam et al, ), tree sparrows attacked and ate moderate numbers of ladybird larvae. It was previously shown that P. montanus ate ladybirds without significant physiological problems, whereas cadavers of P. major from the same experiments showed evidence of severe liver damage (Kristin, ; Marples et al, ).…”
Section: Discussionmentioning
confidence: 79%
“…Even closely related species may have different impacts on populations of aposematic prey owing to specific foraging strategies (Brower, ) or may differ in the origin of avoidance (Exnerová et al, ). In our previous laboratory experiment, experienced great tits captured in winter often avoided larvae of H. axyridis (Aslam et al, ). The results of the current study confirm the avoidance of H. axyridis larvae by experienced wild birds during the breeding season, and in an aviary by naïve birds, and quantify the predation rate of aposematic larvae in comparison to less aposematic and cryptic larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few insects have been proven to be warning colors. One is the toxic two-spotted ladybird beetle, Adalia bipunctata (Linnaeus, 1758), which has warning colors at all stages of its life cycle [ 9 ], and the other is the unpalatable moth, Ivela auripes (Butler, 1877), which pupates at the exposed sites such as tree trunk and rock surface above the ground and displays the conspicuous yellow pupal body with seven longitudinal stripes of blackish dots [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coccinella septempunctata caused toxic effects and resulted in severe liver damage in the nestlings of blue tits Cyanistes caeruleus [6]. Other studies of bird-ladybird interactions showed strong repellence effect precluding feeding the beetles and thus manifestation of their real toxicity (by tits Parus major, domestic chicks) or no effect after ingestion (in sparrow Passer montanus [10]). Ladybird re ex blood has been also found distasteful to ants [7,11,12].…”
Section: Introductionmentioning
confidence: 99%